Northern exposure. Season six [videorecording (DVD)]. - Morrow, Rob; Turner, Janine, 1963-; Corbett, John, 1961- (Universal Studios Home Entertainment, 2014)
Reunite with Dr. Joel Fleischman, Maggie, Chris and the rest of the beloved and quirky residents of Cicely, Alaska, as they take on evil spirits, cannibalistic ancestors and the birth of a new resident.